1969
DOI: 10.1111/j.1365-2672.1969.tb00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Production of Staphylococcal Lipase

Abstract: Summary Lipase production by the cells of Staphylococcus aureus is affected by aeration, agitation, age and pH value of the cultures during growth. At 37° the maximum production of both cells and lipase occurred within the pH range 6.5–9.0, with the optimum for cell production at pH 7.5–8.0 and the optimum for lipase production at pH 7.5–9.0. The presence of air was essential for lipase production, and the maximum lipase activity was produced in a culture incubated 5 days with agitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

1974
1974
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…The strategy used for nucleotide sequencing is shown in Fig. 2 (28), it is likely that the codon at position 706 is the actual initiation codon. Furthermore, it is preceded 4 bp upstream by a potential Shine-Dalgarno sequence (GAGGTGAT) which matches exactly with the 3' terminus of E. coli 16S rRNA (23,25).…”
Section: Resultsmentioning
confidence: 99%
“…The strategy used for nucleotide sequencing is shown in Fig. 2 (28), it is likely that the codon at position 706 is the actual initiation codon. Furthermore, it is preceded 4 bp upstream by a potential Shine-Dalgarno sequence (GAGGTGAT) which matches exactly with the 3' terminus of E. coli 16S rRNA (23,25).…”
Section: Resultsmentioning
confidence: 99%
“…Usually the lipase produced by yeasts stays inside the cell (bound to the cell wall) and it is only secreted to the culture medium when the carbon source has been completely consumed, i.e, in the stationary phase of growth (PereiraMeirelles et al, 2000). The amount of oxygen available to the microorganisms seems to be also an important parameter, since many authors have shown the dependence of lipase productivity on system aeration and agitation (Chen et al, 1999;Elibol and Ozer, 2000;Vadehra and Harmon, 1969). The aim of this work is to evaluate the effects of perfluorodecalin addition on lipase production by Y. lipolytica, considering the improvement in oxygen supply.…”
Section: Introductionmentioning
confidence: 99%
“…33 Lee e Rhee 34 conseguiram aumentar a produção de lipase a partir da bactéria Pseu domonas putida sob condições distintas de aeração e agitação. Elibol e Ozer 3 obtiveram aumento da produtividade da lipase produzida pelo fungo Rhizopus arrhizus aumentando a taxa de aeração.…”
Section: Resultsunclassified